Overview on Niosome - Sanket, Kapse; Prakash, Jadhav; Vivekkumar, Redasani (Asian Journal of Pharmaceutical Research and Development, 2023)
Pharmaceutical such achemicals can be administered locally to sick locations using target-specific drug-delivery devices.Some of the carriers used in various drug delivery techniques includesynthetic polymers, serum proteins, and immune globulins, liposomes, and microspheres. Niosomes' vesicular system, which features a bilayer structure made possible by nonionic surfactants, has the capacity to extend the time that a medicine is accessible in a specific region .Capturing hydrophilic molecules in niosomes or lipophilic medicines is enhanced by their amphiphilic character. To keep the niosomes' structure rigid, additional chemicals like cholesterol can be added. The key features of niosomes, such as their structural components, production methods, limitations, and current applications to a range of the narrative review mentions disorders briefly.